Financial accounting and reporting fundamentals - Cabrera, Ma. Elenita Balatbat; Cabrera, Gilbert Anthony B.; Cabrera, Bernadette Ann B. (Manila : GIC Enterprises & Co. , Inc., 2022)
"The real focus of this textbook in "Financial Accounting and Reporting Fundamentals" is uncovering the meaning of accounting information and how this information is used by decision makers. Throughout this text, we provide you with financial accounting concepts and new elements to develop the reader's ability to understand accounting information in service, trading and manufacturing enterprises by understanding the economic activities that the information describes."
Includes appendix, glossary, subject index and references.
English.
Keywords: Financial accounting; Accountancy